PENGARUH GAYA KEPEMIMPINAN TRANSFORMASIONAL DAN IKLIM ORGANISASI TERHADAP DISIPLIN KERJA KARYAWAN PERGURUAN TINGGI SWASTA KEPERAWATAN DI PONTIANAK - Lukita, Yenni; Syukri, M.; Marmawi, Marmawi (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractEmployeesâ€™ work discipline will be able to be advanced, along with the organization of activities that are managed by leaders who have the ability and intelligence in managing various activities that are carried out well, and composed. From the data obtained by researcher, as one of the components in work discipline, it is found that there is an increasing number of delays at STIK Muhammadiyah Pontianak. This study aimed to describe the effect of transformational leadership style and organizational climate on discipline of work. This study used quantitative approach in the form of descriptive correlational. The sample amounted to 52 people consisting of 25 employees of Dharma Insan Nursing Academy Pontianak and 27 employees of STIKES YARSI Pontianak, who were chosen using saturated sampling techniques. Data retrieval was done by questionnaire instrument using a Likert scale. Data were analyzed using F-test and multiple regression tests. This descriptive analysis shows that the transformational leadership style variable and work discipline are classified as good, and the organizational climate is classified as conducive. The correlation results described: (1). Leadership style has a significant effect of 0,000 <0,05 on work discipline, (2). Organizational climate has a significant effect of 0.039 <0.05 on work discipline. (3). Contributions of Leadership Style and Organizational Climate to Work Discipline (R = 0.887). In conclusion, the leadership style and organizational climate have a significant effect on the work discipline of employees in private universities in Pontianak.Â Keywords: Organizational Discipline, Transformational Leadership Style, Work Climate,.